Non-linear hydroelastic response of a monopile foundation in regular waves. (October 2020) - Leroy, Vincent; Bachynski, Erin E.; Gilloteaux, Jean-Christophe; Babarit, Aurélien; Ferrant, Pierre
Abstract: This paper presents an original contribution to the coupled hydroelastic simulation of offshore wind turbines foundations. A non-linear coupled simulation tool has been developed to calculate the response of these systems. The hydrodynamic loads are computed by the non-linear potential flow solver WSCN, developed at Centrale Nantes and based on the weak-scatterer theory. The response of the structure is calculated with a finite element analysis tool using an Euler-Bernoulli beam model. The two solvers are tightly coupled. A first case study is presented here. It consists of a uniform monopile foundation in regular waves. Numerical simulations are compared to results obtained with the SIMA software, which uses Morison equation and non-linear wave kinematics. The two simulation tools show a very good agreement in a series of regular waves up to the third-order load harmonic. Higher-order harmonics appear with WSCN in steep waves, which are not computed by SIMA.